GENDER AND REPRESSION REFLECTED IN WASHINGTON-POST ONLINE GLOBAL OPINION BY MONA ELTHAWY - hilda yustitiasari (Balai Bahasa Sumatra Barat, 2018)
Many victims of sexual harassment try to come up in media social which pushed Mona Elthawy as a Moslem and feminist to write her opinion about this case. This research is aimed to found the idea of gender and repression which reflected in the Washington Post’s online global opinion entitle “#Mosquemetoo: What Happened When I was Sexually Assaulted during the Hajj”? written by Mona Elthawy. Technique of data analysis using Fairclough three dimensional approaches which the data is analyzed based on the text structure, discourse practice and sociocultural practice. Gender inequality and repression clearly exposed in her writing which the sentences emphasize to the women and herself as the victim and in her writing she stands for women, since Mona is Moslem and Feminist. The response due to the text written by Mona Eltahawy is positive.